Sustainability factors for e-learning initiatives - Cathy Gunn (Association for Learning Technology, 2010)
This paper examines the challenges that ‘grass roots' e-learning initiatives face in trying to become sustainable. A cross-institutional study focused on local, rather than centrally driven, initiatives. A number of successful e-learning innovations were identified that had been driven by capable teachers seeking solutions to real educational problems. However, most of these remain in a high-risk category for institutions and offer poor rewards to their creators. While they may attract grant funding, these initiatives are typically not well supported in other important ways. Semi-structured interviews were conducted with 30 staff in various academic and support roles from the tertiary sector in New Zealand, who were nationally recognised as e-learning leaders. Analysis of their responses revealed both institutional and cultural barriers to long-term sustainability. The following influences on sustainability were identified and discussed: supportive organisational structures, a vision shared by all and staff accountability. The paper proposes that not all initiatives are sustainable and offer practical strategies for achieving diffusion and continuity through collective action. The paper concludes that there is a need for cross-functional collaboration to accommodate different and sometimes conflicting perspectives. This is just one aspect of the culture change that research shows is needed for e-learning to transform, rather than sit uncomfortably alongside, institutional practice.